A Call for Compassionate Care. Issue 4 (October 2017) - Alexander, Karen
Abstract : Abstract: The Substance Abuse and Mental Health Services Administration (2014) reported that 1.1% of pregnant women used nonprescription opiates (either heroin or prescription pills) in the last 30 days. Methadone and buprenorphine are the most common treatments for opiate addiction in pregnant women. Reasons for seeking opiate maintenance treatment (OMT) include keeping custody of one's children and the hope of developing a healthy parenting relationship. Yet, healthcare organizations and professionals have mixed opinions regarding health promotion within the maternal OMT population. Proper education regarding the growing and complex opiate epidemic continues to remain a void for many healthcare professionals. It is imperative that nurses who regularly interact with women in OMT show compassion and competence. It is important to highlight the universality of the challenges and needs of caring for the OMT population. This Perspectives column will explore and describe the context of maternal nonprescription opiate use and the care mothers in OMT should receive based on established nursing ethical standards.